Comp arison of c yclop legic refraction in ch i ldren w i th different iris c olou r cat eg ories: A cross- sec tio na l survey - Arooj, Aisha; Omair, Qazi Muhammad; Bano, Shazia (Journal of the Pakistan Medical Association, 2024)
To compare the cycloplegic refraction in children with different iris colour categories and age groups. The cross -sectional study was conducted from December 2 022 to June 2023 at the Eye Clinic of Sehat Medical Complex, Hanjarwal, Lahore, and Khizar Eye Centre, Lahore, Pakistan, and comprised hyperopic children aged 5-12 years of either gender. Data regarding age, gender, iris colour, auto -refraction and retinoscopy before and after cycloplegic refraction was collected using a structured proforma. Data was analysed using SPSS 21. Of the 139 subjects, 73(52.5%) were males and 60(47.5%) were females. There were 79(56.8%) subjects aged 5-8 ye ars and 60(43.2%) aged 9 -12 years. The iris colour dis tribution was 23(16.5%) light, 80(57.6%) med ium and 36(25 . 9%) da r k, w ith a mean visual acuity of 0.7 ±0.6. There wa s a signi ficant differe nce in non - cyclopleg ic and cycloplegic refraction for different iris colours and age groups (p<0.05). Children with light iris colour accommodated more and needed a low concentration of cyclopentolate compared to those with m edi u m and dark ir is col ours. More accomm odation was noted among child ren ag ed 9-12 years.